Secrets of the universe : discovering the universal laws of science - Fleisher, Paul.; Keeler, Patricia A. (New York : Atheneum, 1987)
Examines the laws of physics that govern the universe, covering such topics as planetary motion, Newton's three laws of motion, gravity, the behavior of gases, and quantum mechanics. Includes experiments and activities.
Includes index.
Bibliography: p. 208-210.
Keywords: Physics -- Juvenile literature; Physical laws -- Juvenile literature; Physics